DIAGONALISASI MATRIKS UNTUK MENYELESAIKAN MODEL MANGSA-PEMANGSA - Persulessy, Elvinus R. (BAREKENG: Jurnal Ilmu Matematika dan Terapan, 2007)
Diagonalization of a square matrix A is based on the process of finding an invertible matrix P such that , where D is diagonal matrix. Matrix P is construct of eigenvectors which corresponding to every eigenvalue of A. The purpose of diagonalization technique is to make the computing process to solve a predator-prey model more easier